Bioinspired nacre-like alumina with a metallic nickel compliant phase fabricated by spark-plasma sintering - Wat,A; Ferraro,C; Deng,X; Sweet,A; Tomsia,AP; Saiz,E; Ritchie,RO (Small, 2019)
Many natural materials present an ideal "recipe" for the development of future damage-tolerant lightweight structural materials. One notable example is the brick-and-mortar structure of nacre, found in mollusk shells, which produces high-toughness, bioinspired ceramics using polymeric mortars as a compliant phase. Theoretical modeling has predicted that use of metallic mortars could lead to even higher damage-tolerance in these materials, although it is difficult to melt-infiltrate metals into ceramic scaffolds as they cannot readily wet ceramics. To avoid this problem, an alternative ("bottom-up") approach to synthesize "nacre-like" ceramics containing a small fraction of nickel mortar is developed. These materials are fabricated using nickel-coated alumina platelets that are aligned using slip-casting and rapidly sintered using spark-plasma sintering. Dewetting of the nickel mortar during sintering is prevented by using NiO-coated as well as Ni-coated platelets. As a result, a "nacre-like" alumina ceramic displaying a resistance-curve toughness up to ≈16 MPa m½ with a flexural strength of ≈300 MPa is produced.